Application of Generalised Inverse to Regionalisation of National Input-Output Tables - Planning Commission (Planning Commission, 1981)
This paper presents a methodology for deriving regional input-output (I-O) coefficients from national I-O tables using the Generalised Inverse of matrices, addressing the lack of regional survey data. Existing non-survey techniques, such as location quotients, representative coefficients, and the RAS method, often produce inconsistent results. The proposed approach constructs a block diagonal matrix of regional weights, allowing reliable estimation of regional coefficients even when some data are missing. Empirical analysis for 21 Indian regions demonstrates approximately 46% conformity with observed values and explains 65% of variations through regression. The study highlights a practical framework for regional economic planning in data-scarce contexts.
Government of India Planning Commission (UNDP Transport Policy Planning Projects)
Government of India Planning Commission (UNDP Transport Policy Planning Projects)
Keywords: Generalised Inverse; Regional Input-Output Tables; Non-Survey Techniques; National I-O Tables; Regional Coefficients; Moore-Penrose Inverse; Spatial Planning; Regression Analysis; Economic Modelling; India